Effects of Workplace Ergonomics on Productivity in an Offshore Oil Company - Mohammad-Ali Liravi; Vahid Baradaran (Archives of Occupational Health, 2019)
Background: The aim of this study is to investigate the relationship between the principles of ergonomics in both material and immaterial dimensions and employee productivity in (IOOC). Methods: Immaterial dimension of ergonomics was measured by variables such as freedom of activity at work and job feedback, and the material dimension of ergonomics was measured by factors such as workplace design and body position. The variables of the productivity construct based on the ACHIEVE model include ability, transparency, assistance, incentive, evaluation, credit, and environment. Each of the constructs was measured by an appropriate questionnaire filled out by 170 operational employees of the Company. Descriptive variables were analyzed using Structural Equation Modeling based on the PLS method to investigate the research hypotheses. Results: The level of employee productivity and ergonomics of the workplace in the IOOC are not desirable due to difficult working conditions and lack of managers' paying attention. The hypothesis of the effectiveness of ergonomics on productivity was confirmed and the material dimension was more effective on employee productivity than the immaterial dimension of human factors. Conclusion: Due to the difficult conditions of the operational units of oil companies, attention should be directed to the physical conditions of the work environment. To improve employee productivity, certain plans for human resource development and management, revision of the designing of the work environment, and work measurement are proposed.